Nuciferine Inhibits TMEM16A in Dietary Adjuvant Therapy for Lung Cancer - Bai, Xue; Liu, Xinyi; Li, Shuting; An, Hailong; Kang, Xianjiang; Guo, Shuai (Journal of agricultural and food chemistry, 2022)
Lung cancer is a malignant tumor with the highest morbidity and mortality rates. Food therapy is a common adjuvant treatment for lung cancer due to its safety and painlessness. Developing new functional food and exploring novel drug targets is important for lung cancer adjuvant therapy. This study confirmed that the active ingredient nuciferine of the lotus leaf was a novel TMEM16A inhibitor by whole-cell patch clamp experiments and site-directed mutagenesis experiments. CCK8 assay, colony formation assay, wound healing assay, and Annexin-V assay were combined to prove that nuciferine inhibited the proliferation and migration of lung cancer cells and promoted cancer cell apoptosis by targeting TMEM16A. Moreover, the combination of nuciferine and cisplatin significantly enhanced the anti-cancer effect of cisplatin. In addition, the signal transduction pathway of nuciferine regulating LA795 cell proliferation, migration, and apoptosis was confirmed by western blot experiments. In vivo experiments showed that nuciferine was a safe and effective natural anti-cancer product for lung cancer. Tissue section pathological detection and pharmacokinetic experiments verified that intragastric administration of nuciferine significantly enhanced the cancer therapy effect of cisplatin and counteracted the toxicity of high concentrations of cisplatin. Therefore, nuciferine is an ideal functional food for adjuvant lung cancer treatment.